Spirit witch eaudiobook - Harper, Helen (Lazy Girl's Guide to Magic, 2017)
Barely recovered from her brush with necromancy, Ivy is flung once more into a world of intrigue, adventure, and potential death and disaster. It's not her fault—it just so turns out that she's now the only person in the entire world who can communicate with the dead. And they're a chatty bunch with a list of demands. When the ghosts offer information about a witch-hating mass murderer in return for Ivy's help, she has no choice but to get involved. She might be getting herself into more trouble than she realizes, though—and that's even before she's dragged to Sunday dinner so she can meet Winter's family . . .